The Role of Participatory Budgeting Management in Reducing the Budget Slack in an Islamic Education Institution - Ekaningrum, Ifada Retno; Hadi, Nor (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This study aims to explore participatory-based budgeting procedures and their role in reducing budgetary slack in Islamic boarding schools. Using a qualitative approach, the research method was conducted at a pesantren-based madrasah in the City of Kudus involving foundation administrators, school principals, leaders, teachers, and plan participants. Primary and secondary data were collected through interviews, observation, and documentation. The data were then analyzed using descriptive analysis. The findings of this study reveal that budgeting in Islamic boarding schools is based on participatory budgeting. Bottom-up budgeting is done from the lowest unit in the organization. The lower unit is the party with a deeper understanding of the smallest practical problems. Having the same responsibility for preparing the budget, lower units are expected to allocate budget items proportionally. Even though we hope that the participatory pattern will not cause slack, the facts show the potential for budgetary slack. This relaxation occurred because of a conservative attitude to anticipate uncertain conditions.